MENYIKAPI ISSUE KELEMBAGAAN KERJASAMA ANTAR DAERAH DI TENGAH LOMPATAN KOLABORASI STRATEJIK GLOBAL: SEBUAH PROGNOSA AWAL - Haris Faozan1 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Inter-region cooperation has become a renowned strategy during local autonomy era to improve public services and social welfare. However, the facts show that cooperation among regions remains a rethoric for more than four decades. Most local governments do not take the concept seriously. Law No. 32 Year 2004 explicitly points out the necessity of Inter-region Cooperation Board but no regulation has been made to support the policy. Therefore, it is time for the government to follow up the policy through creative and innovative mesures in order to instigate inter-region cooperation through a govermental body named Inter-region Cooperation Board.